When Pediatric Headaches Are Not Benign-Eye Findings - Sam Karimaghaei; Brita S. Rook (MDPI AG, 2023)
Headache is the most common neurologic complaint that presents to the pediatrician. While most headaches are benign in nature, patients must be carefully evaluated to rule out life- or vision-threatening causes. Non-benign etiologies of headache may exhibit ophthalmologic signs and symptoms that can help narrow the differential diagnosis. It is also important for physicians to know in what situations appropriate ophthalmologic evaluation is necessary, such as evaluating for papilledema in the setting of elevated intracranial pressure. In this article we discuss life- and/or vision-threatening etiologies of headache, including infection, autoimmune disease, cerebrovascular pathologies, hydrocephalus, intracranial neoplasia, and idiopathic intracranial hypertension, and their associated ophthalmologic manifestations. Due to less familiarity of the disease amongst primary care providers, we discuss pediatric idiopathic intracranial hypertension in more comprehensive detail.